Effect of Service Quality on Brand Credibility, Emotional Attachment, and Customer Advocacy in Omni-Channel Marketing - Sasmita, Muhamad Utsman Adi (Fakultas Ekonomi Universitas Garut, 2024)
This study aims to examine the effect of service quality on perceived brand credibility and emotional attachment, as well as its impact on customer brand advocacy in the context of omni-channel marketing. Additionally, this study investigates the role of prior experience as a moderating variable on the Galatea Parfum brand. Data were collected from 290 respondents who are consumers from the millennial and Gen Z generations. The data analysis technique used the Structural Equation Modeling (SEM) method with the help of AMOS version 24 software. The results show that service quality significantly influences perceived brand credibility and emotional attachment, which in turn positively affects customer brand advocacy. Prior experience has been proven to strengthen the relationship between service quality and both perceived brand credibility and emotional attachment